Model Pengembangan Kompetensi Sikap Sosial Pada Siswa Sekolah Dasar - Ani Siti Anisah; Sapriya Sapriya; Kama Abdul Hakam; Ernawulan Syaodih (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2022)
This study aims to analyze and describe the factual conditions of the social attitude development model of students in elementary schools. The research method used is a descriptive qualitative approach. This research was conducted through several activities (1) Observation, distributing questionnaires and interviews to principals and teachers with the main objective of obtaining factual information about the attitude development model in elementary schools, (2) Studying documents, analyzing school identity documents, and learning tools with The goal is to get an overview of the learning objectives to be achieved. (3) Literature review to find a theoretical basis on the development of an attitude development model that fits the needs of students. The results of the study describe that the model of developing students' social attitudes is carried out through school policies in internalizing character values ??through supporting activity programs; (1) routine activities are carried out regularly with the aim of forming students' habits of doing things well, (2) spontaneous activities, (3) exemplary activities, (4) annual program activities, (5) nationalism activities, (6) outdoor learning activities and training. The teacher's role as implementer and evaluator in the development of students' social attitudes is realized in the learning process in the classroom starting from the preparation of lesson plans in character-based designs. Attitude development is carried out through a scientific learning approach through the stages of observing, asking questions, gathering information, associating information, and communicating learning outcomes. This approach is able to bring students to learn to think critically about moral and social issues so that good social attitudes are formed which are shown in the process of social interaction in the community. The model for developing students' social attitudes by teachers and schools in internalizing and disseminating character values through modeling, conditioning, and habituation approaches.